Validation of a lifestyle questionnaire for physicians specialists before and during the COVID-19 pandemic - Salcedo-Hermoza, Sandra Teresa (2022)
Introduction. Isolation and social distancing strategies to control the COVID-19 pandemic probably had a negative impact on physicians’ lifestyles. Objective. To design and validate a questionnaire to assess physicians’ lifestyle before and during the pandemic. Methods. We carried out a psychometric study. A total of 204 medical specialists from a national hospital in Lima-Peru were admitted to the study and answered the questionnaire virtually. Results. Content validity was carried out with a committee of experts, with a Cochran’s Q of 7 and p of 0.50. In the relevance, representativeness and clarity of the items, the global Aiken’s V was 0.97. The pilot test showed adequate reliability (Cronbach’s alpha 0.842). For construct validity, overall sample adequacy was assessed by Bartlett’s test of sphericity, before (X2=4235.75, p<0.01) and during (X2=4328, p<0.01) the pandemic. In addition, the Kaiser-Meyer-Olkin (KMO) test had an overall value before and during the pandemic of 0.78 and 0.76 respectively. Exploratory Factor Analysis structured five domains. Factor loadings (polychoric correlations and Oblimin rotation) were estimated, and the correlation between domains was adequate. Confirmatory Factor Analysis indicated adequate model fit. Conclusion. The instrument shows adequate psychometric properties, so it can be considered as a useful, valid, and reliable instrument to assess the lifestyle of physicians before and during the COVID-19 pandemic.